Morphological and microstructural evolution of high-quality PbSe epitaxial film on Si substrate by chemical bath deposition. (1st November 2022) - Liu, Yun; McDowell, Lance L.; Su, Leisheng; Luo, Yingmin; Qiu, Jijun; Shi, Zhisheng
Abstract: High-quality lead selenide (PbSe) epitaxial films are key to improving the performance of mid-wave infrared (MWIR) optoelectronics. Herein, high-quality PbSe epitaxial films with 30 μm in thickness were successfully fabricated by chemical bath deposition (CBD), and the growth modes were described by investigating the effect of growth temperature and [OH − ]/[Pb 2+ ] on the morphologies and microstructural evolution of PbSe epitaxial films. Furthermore, a new pre-orientation induced oriented attachment (POIOA) growth mechanism was proposed to illustrate the texture of close-packed PbSe (111) nano-pyramids. It was found that the film orientation is determined by the epitaxial seed layer and the growth mechanism varies with temperature changing from the low-temperature cluster mechanism (LTCM, < 30 °C) to the middle-temperature POIOA (30–60 °C) mechanism, and finally dominated by high-temperature ion-by-ion (HTIBI, > 60 °C) which was crucial for single-crystal PbSe deposition. The increased [OH − ]/[Pb 2+ ] can significantly decrease the transformation-temperature of the growth mechanism, and the single-crystal film can be obtained as the temperature reaches 40 °C. Eventually, a microstructural zone model of films as a function of temperatures and [OH − ]/[Pb 2+ ] was established.